Patient position and hypoxemia during propofol sedation for colonoscopy: a randomized trial - Klare, Peter; Reindl, Wolfgang (Endoscopy, 2015)
Aim: To evaluate the benefits of the left lateral position in avoiding hypoxemic events in patients undergoing colonoscopy. Methods: We conducted a randomized, prospective, controlled trial at two study sites in Germany. Patients undergoing colonoscopy under propofol sedation were randomized to either the supine or left lateral position. The primary outcome was oxygen desaturation (SaO2 < 90 %). Secondary outcome measures were apneic events, hypotension, patient satisfaction, propofol dosage, cecal intubation time, and adenoma detection. Results: A total of 412 patients were randomized 1:1 to undergo colonoscopy in the supine or left lateral position. No severe adverse events were observed in either group. Intention-to-treat analysis revealed no significant difference in the frequency of desaturation in the left lateral arm compared with the supine arm (6.8 % vs. 12.1 %; P = 0.064). Patients in the left lateral arm showed lower apnea rates (9.4 % vs. 16.2 %; P = 0.040), but had more episodes of hypotension (12.3 % vs. 2.9 %; P < 0.001). The frequency of repositioning was higher in the left lateral group. No significant differences were observed in patient satisfaction and cooperation, propofol dosage, or adenoma detection rate. Patients who were repositioned to facilitate endoscope passage were excluded from per-protocol analysis. The incidence of hypoxemia was lower for the left lateral than for the supine group in per-protocol analysis (1.8 % vs. 11.2 %; P = 0.003). Conclusion: The positioning of patients in the left lateral position during propofol sedation for colonoscopy results in lower desaturation rates provided the position can be maintained throughout endoscopy. ClinicalTrials.gov NCT02001792.